MeJA Elicitation of Chicory Hairy Roots Promotes Efficient Increase of 3,5-diCQA Accumulation, a Potent Antioxidant and Antibacterial Molecule - Guillaume Bernard; Harmony Alves Dos Santos; Audrey Etienne; Jennifer Samaillie; Christel Neut; Sevser Sahpaz; Jean-Louis Hilbert; David Gagneul; Nathalie Jullian; Ali Tahrioui; Sylvie Chevalier; Céline Rivière; et al. (Antibiotics, 2020)
Cichorium intybus L. (Asteraceae) is an important industrial crop, as well as a medicinal plant which produces some bioactive compounds implicated in various biological effects with potential applications in human health. Particularly, roots produce hydroxycinnamic acids like 5-caffeoyquinic acid and 3,5-dicaffeoylquinic acid (di-CQA). The present investigation relates to the use of methyl jasmonate for enhancing phenolic compounds accumulation and production in hairy root cultures of C. intybus. Elicitated hairy root growth rate increased 13.3 times compared with the initial inoculum in a period of 14 days and di-CQA production represented about 12% of DW. The elicitation has also promoted the production of tricaffeoylquinic acid never described in the chicory roots and identified as 3,4,5-tricaffeoyquinic acid by means of nuclear magnetic resonance. Our study confirmed the strong anti-oxidant effect of di-CQA. Our results also confirmed globally a selectivity of action of di-CQA against Gram-positive bacteria, in particular against some strains of Staphylococcus and Streptococcus. However, a non-negligible antibacterial activity of di-CQA against Pseudomonas aeruginosa was also underlined (MIC = 0.156 mg.mL−1 against some P. aeruginosa strains). The influence of di-CQA has been explored to evaluate its impact on the physiology of P. aeruginosa. Di-CQA showed no effect on the biofilm formation and the production of extracellular pyocyanin. However, it demonstrated an effect on virulence through the production of pyoverdine with a dose-dependent manner by more than 7-fold when treated at a concentration of 128 µg·mL−1, thus suggesting a link between di-CQA and iron sequestration. This study shows that elicitated hairy root cultures of chicory can be developed for the production of di-CQA, a secondary metabolite with high antibacterial potential.